2,6-Di-terc-butilfenola grupu saturošu zāļu vielu sintēze un struktūras noteikšana ar rentgenstruktūranalīzes metodēm - Sakaine, Guna (Latvijas Universitāte, 2013)
Darbā raksturota 2,6-di-terc-butilfenola grupu saturošu zāļu vielu sintēze un farmakoloģiskā nozīme, polimorfisms, rentgendifrakcijas pamatprincipi, īpašu nozīmi pievēršot struktūras noteikšanai ar pulvera difrakcijas metodi. Darba praktiskajā daļā sintezētas piecas zāļu vielas: tazofelons, S-2474, E-5110, R-830 un KME-4. No monokristāla difrakcijas noteikta KME-4 un S-2474 kristāliskā struktūra. KME-4 struktūra noteikta arī no pulvera difrakcijas. Darbā iegūta jauna S-2474 polimorfā forma.

The synthesis and pharmaceutical relevance of 2,6-di-tert-butyl phenol group containing drugs is desribed in the thesis. Polymorphism, the principles of X-ray crystallographic analysis are also discussed, placing a special emphasis on structure determination from powder diffraction. Synthesis of five pharmaceutically relevant drugs – tazofelone, S-2474, E-5110, R-830 and KME-4 – is accomplished and presented in the experimental part. The crystalline structures of KME-4 and S-2474 have been determines using the single crystal diffraction. The structere of KME-4 has also been determined from powder diffraction. A novel polymorph form of S-2474 has been obtained.
Synthesis and structure determination of 2,6-di-tert-butyl phenol group containing drugs using X-ray crystallographic analysis
Keywords: Ķīmija